1987
DOI: 10.1007/bf02555127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aluminum(III), chromium(III), and iron(III) on the rate of dissolution of calcium hydroxyapatite crystals in the absence and presence of the chelating agent desferrioxamine

Abstract: Aluminum ions (Al) and chromium (III) ions (Cr), as they exist in aqueous solution at neutral pH, adsorb onto calcium hydroxyapatite crystals (HAP) and severely inhibit their dissolution process, when present in concentrations less than 1 microM. Iron (III) ions (Fe), at concentrations up to 10 microM, have no effect on the dissolution process of HAP. The Fe-chelating agent desferrioxamine also forms strong complexes with Al but not with Cr. Desferrioxamine prevents the adsorption of Al to HAP and removes pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…1016/j.gca.2008.09.009 for an inert metal center like chromium. It is worth noting that the frequency of dehydration of water from Cr(III) is 10 À6.3 s À1 , compared with 10 À0.8 s À1 for Al(III) and 10 3.5 s À1 for Fe(III) (Christoffersen et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…1016/j.gca.2008.09.009 for an inert metal center like chromium. It is worth noting that the frequency of dehydration of water from Cr(III) is 10 À6.3 s À1 , compared with 10 À0.8 s À1 for Al(III) and 10 3.5 s À1 for Fe(III) (Christoffersen et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The in hibition of seeded crystal growth [Gilbert et al, 1989] and dissolution [Brudevold, 1963] by zinc and other polyvalent metal ions [Legeros et al, 1980;Christoffersen et al, 1987] is well documented. We find, however, that crystal growth inhibition by zinc appears to take place only above a threshold surface concentration of around 3 pmol Zn/m2 and does not increase further with the zinc concentration.…”
Section: Inhibition O F Seeded Crystal Growth By Zinc Ionsmentioning
confidence: 99%
“…In addition to the antiplaque effect, however, in common with a number of polyvalent metal ions and metal-ion/organic-ligand complexes [Christoffersen et al, 1987;Meyer and Thomas, 1982], zinc adsorbs onto the surface of calcium phosphate phases, inhibiting hydroxyapatite (HAP) crystal growth Zn remaining in solution, mM [Legeros et al, 1980;Meyer and Angino, 1977;Bachra and van Harskamp, 1970;Bird and Thomas, 1963], Even rela tively young plaques contain amorphous calcium phos phate crystallites which subsequently convert to HAP via brushite [Kaufmann and Kleinberg, 1973;Driessens and Verbeeck, 1989], Similarly, Brudcvold et al [1963] found that zinc was adsorbed onto the surface of both HAP and human enamel, displacing calcium.…”
mentioning
confidence: 99%
“…0.001), many samples obtained by sucking modified candy showed no signs of HAp dissolution in spite of being un-tial of solid foodstuffs include the salivary proteins, which via pellicle forming properties can form a diffusion barrier on tooth surfaces that protects against erosion [Meurman and Frank, 1991;Nekrashevych and Stösser, 2003]. But also saliva buffer capacity [Jensdottir et al, 2005b], as well as fluoride, minerals, and metals originating from drinking water, foodstuffs, and oral care products [ten Cate and Duijsters, 1983;Christoffersen et al, 1987] may protect against dental erosion in saliva. In this complex and highly individually determined biological fluid, simple markers for erosion such as pH and saturation level with respect to hydroxyapatite (HAp) may have little explanative power.…”
Section: Introductionmentioning
confidence: 99%